2022
DOI: 10.3389/fendo.2022.1009133
|View full text |Cite
|
Sign up to set email alerts
|

The critical BMI hypothesis for puberty initiation and the gender prevalence difference: Evidence from an epidemiological survey in Beijing, China

Abstract: BackgroundAlthough previous studies suggested that there is a certain level of body fat mass before puberty can be initiated, most studies have focused on girls.ObjectiveTo investigate the relationship between precocious puberty and physical growth in school-aged children in Beijing, China.Methods7590 Chinese children (3591 girls and 3999 boys) aged 6–11 years were recruited in Beijing, China. Body mass index (BMI) categories were defined by WHO Child Growth Standards and central obesity were defined by sex-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Our findings confirm the results of previous reports suggesting that precocious puberty is associated with an increased risk of obesity in girls, while the relationship between precocious puberty and obesity in boys remains inconclusive according to previous studies ( 25 , 36 , 37 ). Previous studies have also shown that boys with precocious puberty are associated with a higher BMI, although the BMI threshold for puberty development in boys is higher than that in girls ( 38 ). During pubertal development, significant sex differences exist between obese girls and boys, with increased peripheral conversion of low-potency androgens to estrogens by adipose tissue-aromatase and increased insulin resistance being two potential contributing factors ( 39 ).…”
Section: Discussionmentioning
confidence: 93%
“…Our findings confirm the results of previous reports suggesting that precocious puberty is associated with an increased risk of obesity in girls, while the relationship between precocious puberty and obesity in boys remains inconclusive according to previous studies ( 25 , 36 , 37 ). Previous studies have also shown that boys with precocious puberty are associated with a higher BMI, although the BMI threshold for puberty development in boys is higher than that in girls ( 38 ). During pubertal development, significant sex differences exist between obese girls and boys, with increased peripheral conversion of low-potency androgens to estrogens by adipose tissue-aromatase and increased insulin resistance being two potential contributing factors ( 39 ).…”
Section: Discussionmentioning
confidence: 93%
“…This controversial results would be attributed to the study design, evaluation technique different populations studied and study duration. In justifying the obtained results for boys, it should be noted that there are conflictary results regarding the relationship between obesity and timing of pubertal onset in boys ( 40 , 41 ) and this can be a reason for low correlation of obesity and maturity in boys rather than girls. In other words, obesity would contribute to early onset of puberty in girls more than boys.…”
Section: Discussionmentioning
confidence: 85%
“…In other words, obesity would contribute to early onset of puberty in girls more than boys. One possible reason for this effect refers to higher threshold of BMI for puberty development in boys than girls ( 41 ). The second aim was to examine the effects of anthropometric measurements, gender, and obesity on biological maturation in adolescents.…”
Section: Discussionmentioning
confidence: 99%